The voice and swallowing profile of adults with laryngotracheal stenosis before and after reconstructive surgery: a prospective, descriptive observational study - Clunie,G; Roe,J; Al-Yaghchi,C; Alexander,C; McGregor,A; Sandhu,G (Clinical Otolaryngology, 2024)
Objectives:Airway reconstruction for laryngo tracheal stenosis (LTS) improves dyspnoea. There is little evidence relating to impact upon voice and swallowing. We explored voice and swallowing outcomes in adults with LTS before and after reconstructive surgery.Design:Outcome measures were collected pre-reconstructive surgery, two-weeks post-surgery and up to 4-6 months post-surgery.Setting:Tertiary referral centre.Participants:With ethical approval, twenty consecutive adult (≥18 years) LTS patients undergoing airway reconstruction were prospectively recruited.Main outcome measures:These included physiological values (maximum phonation time (MPT) and fundamental frequency; penetration aspiration score, residue score), clinician-reported (GRBAS, functional oral intake score, 100ml Water Swallow Test) and patient-reported outcomes (Voice Handicap Index-10, Reflux Symptoms Index, Eating Assessment Tool, Dysphagia Handicap Index).Results:The observational study identified patient-reported and clinician-reported voice and swallow difficulties pre- and post-surgery; median and interquartile range are reported at each time point: Voice Handicap Index-10 23 (8-31); 20.5 (9-33.5), 24.5 (12.5-29); Dysphagia Handicap Index 9 (0-37); 13 (7-44); 15 (4-34); GRBAS grade 1(1-2); 2 (1-2.5); 2(1-2); 100ml Water Swallow Test volume score 16.7 (11.1-20); 14.3 (12.5-16.7); 16.7 (14.3-20.0); 100ml Water Swallow Test capacity score 16.3 ± 9.0; 11.0 ± 4.1; 12.5 ± 2.6.Conclusions:We present the first prospective data on voice and swallowing outcomes in adults with LTS before and after reconstructive surgery. The variability of the outcomes was higher than expected but importantly, for many the voice and swallow outcomes were not within normal limits before surgery. The clinical value of the study demonstrates the need for individual assessment and management of LTS patients’ voice and swallowing.